An Efficient Fault Tolerance Model for Single and Multi-Fault in MPLS Networks - Al-Fuhaidi, Belal A.; Asaad, Hasan A. A.; Al-Taweel, Sadik (Universiti Malaysia Pahang Al-Sultan Abdullah Press, 2019)
The ever increasing demands for the performance improvement in Multiprotocol Label Switching (MPLS) network have motivated to develop a resistant MPLS network to the failures at link, node and software of the MPLS network devices. The occurrence fault at link degrades the network performance due to data packets loss. This paper proposes an efficient model for rerouting traffic in MPLS network when a single and multi-fault occur in working link based on the protection switching and rerouting algorithms. In this model three algorithms are developed for fast fault recovery in MPLS network based on ingress LSR, alert LSR and core LSR. The proposed model has been simulated using Network Simulator (NS2) version 2.34, simulation results show that the proposed model significantly improves the network performance such that eliminates packet disorder, reduces the packets loss, get better PDR, decreases end to end delay and enhance throughput. The proposed model has less space complexity compared to other methods that reached to 13.33% in single fault and 33.33% in multi-fault and has a fast recovery time compared to other methods.